(untitled) (The Peerian Journal, 2024)
The article discusses new scientific approaches to the laws of vehicle movement on a mountain road and their analysis in a new interpretation. The results of scientific research related to improving traffic safety in extreme road conditions are presented. Scientific proposals are given